(6•2 - 3 - 5•3) - (4•3 + 2•2 - 8)
(12 - 3 - 15) - (12 + 4 - 8)
(9 - 15) - (16 - 8)
(-6) - (8)
-14
Answer:
x=36
Step-by-step explanation:
17+3 =20
now we have :
x+4
___ = 20
2
20*2= 40
x+4=40
x=36
hopes this helps
Answer:
That would be a decrease of 40%
Step-by-step explanation:
She has 630 blue beads and 45 red beads. Equation is x + 14x = 675
Answer:
5.4
Step-by-step explanation:
Using the pythagorean theorem (a^2 + b^2 = c^2), we can do 2^2 plus 5^2, which is 4 + 25, which simplifies to 29. Now we have 29 = c^2
In order to find c (the hypotenuse), we need to take the square root of both sides to find c. Thus, c = sqrt 29 or 5.385...
Hope this helps!